Transversus abdominis plane block in oncourology: a narrative review - S. B. Petrov; K. A. Nikulina; A. V. Arnautov; S. A. Reva (Вестник урологии, 2025)
Transversus abdominis plane block (TAP block) is a regional anesthesia technique used as part of multimodal postoperative analgesia for a wide range of abdominal surgical procedures. However, the use and effectiveness of this technique in urological surgeries are not well documented in Russian literature. We conducted a literature search in PubMed, EMBASE, Web of Knowledge, and Cochrane Library databases to evaluate the effectiveness of using transversus abdominis plane blocks compared to other anesthesia techniques in oncourological surgery. It has been determined that transversus abdominis plane block, serving as an integral component of multimodal anesthesia in patients undergoing oncourological procedures, significantly curtails the reliance on opiates both during and following surgery. Moreover, it mitigates the intensity of pain syndrome in the postoperative phase and fosters a swifter and more comprehensive recovery process for patients.